Follow-up of dairy cattle naturally infected by Trypanosoma vivax after treatment with isometamidium chloride - Castilho Neto, Kayo José Garcia de Almeida [UNESP]; Garcia, Ana Beatriz da Cruz Favaro [UNESP]; Fidelis Junior, Otavio Luiz; Nagata, Walter Beterquini [UNESP]; André, Marcos Rogério [UNESP]; Teixeira, Marta Maria Geraldes; Machado, Rosangela Zacarias [UNESP]; Cadioli, Fabiano Antonio [UNESP] (FapUNIFESP (SciELO), 2021)
Trypanosoma vivax infections cause nonspecific clinical signs in cattle associated with aparasitemic intervals, making disease diagnosis a challenge. In Brazil, diminazene aceturate and isometamidium chloride (ISM) are available to treat bovine trypanosomosis. The objective of this study was to follow-up, by molecular and serological techniques, dairy cattle naturally infected by T. vivax after ISM treatment. Thirty cattle naturally infected with T. vivax received two applications of ISM, at a dosage of 1.0 mg/kg intramuscularly, on days 0 and 150. For T. vivax diagnosis, EDTA-blood and serum samples were evaluated on 0, 7, 15, 30, 60, 90, 120, 150, 180, 210, and 240 days after treatment PCR, Loop-mediated isothermal amplification (LAMP) and ELISA. Animals with persistent detection of T. vivax DNA by both PCR and LAMP were found and continuous detection of anti-T. vivax IgG antibodies by ELISA, suggesting the presence of T. vivax resistance to ISM. The combination of LAMP and ELISA tests can prevent misdiagnosis of the parasite clearance in treated cattle, contributing to better disease control. This is the first experiment that demonstrates the persistence infection of T. vivax under ISM treatment in a natural infected herd and evidence of ISM chemotherapy-resistant T. vivax in Brazil.